Molecular Evaluation of the Novel Coronavirus Infection of Cockroaches and Flies Collected from Kamkar-Arabnia Hospital in Qom City, Central Iran: With Innovated Internal Control - Abedin Saghafipour; Reza Fotouhi-Ardakani; Majid Kababian; Melika Alirezaei; Hassan Vatandoost (Tehran University of Medical Sciences, 2022)
Background: Due to the confirmation of the presence of the novel coronavirus in the feces and municipal sewerage system, and the feeding of domestic insects from fecal matter, as well as the ability of these insects to mechanically transmit microbes from the sewerage system. This study was aimed at molecular evaluation of the novel coronavirus infection isolated on cockroaches and flies collected from Kamkar-Arabnia Hospital in Qom City, Iran. Methods: Totally, 18 samples; (12 samples cockroaches and 6 flies) from the external surface of cockroaches and houseflies as well as their digestive system were prepared. After designed and synthetized exogenous heterologous internal control, the RNA was extracted to investigate the contamination of these samples with the novel coronavirus. To detect the virus, the E and RdRp genes were identified. Results: Investigation of coronavirus E gene using the multiplex one-step qPCR technique on the collected samples showed an amplification plot in CT= 35.70 related to the internal surfaces of cockroaches collected from the treatment and sick room of the hospital. Also, the design of internal control to ensure the accuracy of the extraction process was successful. Conclusion: According to the findings of the present study regarding detecting the presence of the coronavirus infection in the digestive system of domestic insects such as American cockroaches and considering their ability to mechanically transmit viruses, it is recommended to control the domestic insects that are in close contact with humans in crowded places such as hospitals and health centers during the Covid-19 pandemic.